2021
DOI: 10.1007/s11255-020-02758-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease predicts poor outcomes of COVID-19 patients

Abstract: Purpose The recent outbreak of COVID-19 rapidly spread worldwide. Comorbid diseases are determinants of the severity of COVID-19 infection and mortality. The aim of this study was to explore the potential association between chronic kidney disease (CKD) and the severity of COVID-19 infection. Methods The study included 609 consecutive adult patients (male: 54.52%, mean age: 59.23 ± 15.55 years) hospitalized with the diagnosis of COVID-19 in a tertiary leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…In the cohort of Gok et al, including 609 consecutive adult patients hospitalized with a diagnosis of COVID-19 in a tertiary-level hospital, the percentage of patients with low eGFR was close to 21%, rather similar to our finding [18]. A quarter of the evaluated patients showed AKI [18].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the cohort of Gok et al, including 609 consecutive adult patients hospitalized with a diagnosis of COVID-19 in a tertiary-level hospital, the percentage of patients with low eGFR was close to 21%, rather similar to our finding [18]. A quarter of the evaluated patients showed AKI [18].…”
Section: Discussionsupporting
confidence: 89%
“…In line with these findings, Uribarri et al showed an increased risk for in-hospital complications and mortality among patients with renal failure [15]. Similarly, according to Gok et al, both AKI and CKD are independently associated with mortality [18]. On the contrary, Bravi et al, did not find eGFR to be an independent predictor of poor outcomes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The incidence of in-hospital mortality in this study was 18%. As already described by other authors [15][16][17], the presence of reduced renal function increases mortality rate. In most studies, CKD is defined as the presence of eGFR <60 mL/min, with no further differentiation between the various stages of renal disease.…”
Section: Discussionsupporting
confidence: 58%
“…Later observational data suggest that patients with CKD are at higher risk for severe COVID-19 disease and mortality during admission, ranging from 2.1-fold [95% confidence interval (CI): 1.36-3.26] higher for elevated serum creatinine, to 3.9-fold higher (95%CI: 2.57-6.14) for elevated blood urea nitrogen levels [15]. These observations have been confirmed in several subsequent studies [41][42][43]. In the largest study, including > 17 million primary care records from the United Kingdom (UK) and 10,926 COVID-19-related deaths, patients with estimated glomerular filtration rate (eGFR) 30-60 ml/ min/1.73 m 2 [Hazard Ratio (HR): 1.33, 95%CI: 1.28-1.40] and < 30 ml/min/1.73 m 2 (HR: 2.52, 95%CI: 2.33-2.72) had higher mortality risk compared to those with eGFR > 60 ml/ min/1.73 m 2 , corresponding to mortality rates of 0.4% and 1.11%, respectively [16].…”
Section: Cardiovascular Complications In Ckd Patients With Covid-19mentioning
confidence: 80%